PENGARUH PENGGUNAAN MULTIMEDIA INTERAKTIF TERHADAP PEMAHAMAN KONSEP KEGUNUNGAPIAN ATAU VULKANISME : Studi Eksperimen pada Siswa Kelas X SMA Negeri 16 Bandung - Hartono, - (2012)
Poor students' understanding of the learning concepts that are abstract and difficult to study directly pointed out is one result of the non optimal use of instructional media in SMA Negeri 16 Bandung. One type of learning medium that has the potential to enhance students' understanding of the concepts learned is an interactive multimedia. This study aims to determine (1) differences in students' understanding of volcanism concepts in class using and not using interactive multimedia after treatment is given (2) the response of students towards the use of interactive multimedia (MMI) (3) constraints encountered in implementation of learning with the use of interactive multimedia learning through discussion methods. The research method used is a quasi-experimental design with nonequivalent control group. Theoretical foundation that is used consists of instructional media theory, interactive multimedia, graphic media, understanding and volcanism concepts. Data analysis results of tests performed by t-test statistical techniques and analysis of questionnaire data using the technique percentage. Data analysis of test results showed volcanism understanding of the concept (1) there are differences in test results on students' understanding of volcanism concepts in class using an interactive multimedia before and after treatment (2) there are differences in test results of volcanism understanding of concepts in students in the class who did not use interactive multimedia before and after treatment (3) there were no differences in test results between students 'understanding of volcanism concepts in class using and not using interactive multimedia before treatment (4) there is a difference between students' understanding of volcanism concepts in class using and not using interactive multimedia after treatment. Analysis of questionnaire data results indicate that charging students responded positively to the use of interactive multimedia in teaching volcanism indicated> 70% stated that more motivated and able to better understand the concepts he learned volcanism. Recommendations based on this study, namely (1) should be developed interactive multimedia to other concepts that fit with the character of interactive multimedia and SK / KD / IPS-learning indicators in geography (2) training efforts need to be done to improve teachers' competence-related design and manufacturing multimedia. Key word : interactive multimedia, understanding, volcanism